Trans- and cis-urocanic acid, biogenic amine and amino acid contents in ikan pekasam (fermented fish) produced from Javanese carp (Puntius gonionotus) and black tilapia (Oreochromis mossambicus) - Mohamad Azman, Ezzat; Zare, Davood; Karim, Roselina; Mohd Ghazali, Hasanah (Elsevier, 2015)
Ikan pekasam is a fermented fish product produced in Malaysia and is usually made from freshwater fish with ground roasted uncooked rice as the main source of carbohydrate. In this study, the amino acid, biogenic amine, and trans- and cis-urocanic acid (UCA) contents of fifteen commercial samples of Ikan pekasam made from Javanese carp and black tilapia, that had undergone either natural or acid-assisted fermentation, were quantified. The latter includes either tamarind (Tamarindus indica) pulp or dried slices of Garcinia atroviridis fruit in the fermentation process. Results showed that there are no significant differences in most of the biogenic amines including histamine, while there are significant differences in total UCA content, and trans- and cis-UCA contents between the two samples. Differences in the amino acid contents were largely fish-dependent.